Nucleosome Linker DNA Contacts and Induces Specific Folding of the Intrinsically Disordered H1 Carboxyl-Terminal Domain - Caterino, Tamara L. (American Society for Microbiology, 2011)

(untitled)
Linker histones play essential roles in the chromatin structure of higher eukaryotes. While binding to the surface of nucleosomes is directed by an ∼80-amino-acid-residue globular domain, the structure and interactions of the lysine-rich ∼100-residue C-terminal domain (CTD), primarily responsible for the chromatin-condensing functions of linker histones, are poorly understood. By quantitatively analyzing binding of a set of H1 CTD deletion mutants to nucleosomes containing various lengths of linker DNA, we have identified interactions between distinct regions of the CTD and nucleosome linker DNA at least 21 bp from the edge of the nucleosome core. Importantly, partial CTD truncations caused increases in H1 binding affinity, suggesting that significant entropic costs are incurred upon binding due to CTD folding. van't Hoff entropy/enthalpy analysis and intramolecular fluorescent resonance energy transfer (FRET) studies indicate that the CTD undergoes substantial nucleosome-directed folding, in a manner that is distinct from that which occurs upon H1 binding to naked DNA. In addition to defining critical interactions between the H1 CTD and linker DNA, our data indicate that the H1 CTD is an intrinsically disordered domain and provide important insights into the biological function of this protein.